2020
DOI: 10.1111/aec.12865
|View full text |Cite
|
Sign up to set email alerts
|

Space use and temporal partitioning of sympatric Tasmanian devils and spotted‐tailed quolls

Abstract: Sympatric species can minimise interspecific competition by spatial avoidance or by altering their temporal activity to reduce encounter rates. The Tasmanian devil (Sarcophilus harrisii), the largest carnivorous marsupial, coexists with the smaller spotted-tailed quoll (Dasyurus maculatus) in Tasmania, Australia. Quolls may be susceptible to interspecific competition from devils, because they utilise similar habitats, consume similar prey species and are displaced by devils at food sources. Such competition mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 70 publications
(114 reference statements)
0
20
0
Order By: Relevance
“…this study area [27], which showed that most devils became active at sunset, movement rates gradually reduced after midnight, and most devils were stationary by sunrise. The first hour of footage following the release of a devil from the trap was considered likely to be atypical and was excluded.…”
Section: Plos Onementioning
confidence: 80%
See 3 more Smart Citations
“…this study area [27], which showed that most devils became active at sunset, movement rates gradually reduced after midnight, and most devils were stationary by sunrise. The first hour of footage following the release of a devil from the trap was considered likely to be atypical and was excluded.…”
Section: Plos Onementioning
confidence: 80%
“…Devils were trapped in custom built pipe traps (diameter 315 mm x length 875 mm, constructed from solid PVC pipe; N. Mooney and D. Ralph, unpublished data) baited with meat. Nearly all of the devils on the study site (n = 142) were already microchipped as part of a long term study on devil movement [16,27]. Only devils that have been trapped several times before were fitted with a camera, to ensure a high probability of recapture for collar retrieval.…”
Section: Deploymentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wide‐ranging marsupial carnivores, spotted‐tailed quolls and Tasmanian devils, were recorded throughout the Midlands landscape, including in riparian plantings. Quolls and devils travel daily up to 22 and 8 km, respectively, across a wide range of habitats including paddocks and forest (Andersen et al 2020) and disperse up to 100 km, indicating that no amount of habitat fragmentation in Tasmania presents a significant barrier (Lachish et al 2011; Proft 2019).…”
Section: Discussionmentioning
confidence: 99%